Програмна система для автоматизованого контролю за бджолами - Шаповал, А. А. (ХНУРЕ, 2020)
The given work is devoted to help beekeepers manage with bees. The following functionality will be developed: measuring of level of temperature, humidity, oxygen in beehive. Also the system will count amount of bees. Using all of these credentials system will be able to control process of swarming. Also using average temperature of the day during last years system will be able to advise what to do with beehives (hide them or take out).